Nonlinear change processes and the emergence of suicidal behavior: A conceptual model based on the fluid vulnerability theory of suicide. (April 2020) - Bryan, Craig J.; Butner, Jonathan E.; May, Alexis M.; Rugo, Kelsi F.; Harris, Julia A.; Oakey, D. Nicolas; Rozek, David C.; Bryan, AnnaBelle O.
Abstract: Although ideation-to-action theories of suicide aim to explain the emergence of suicidal behaviors, researchers have primarily focused on the content of underlying mechanisms (i.e., who dies by suicide). Much less attention has focused on the temporal dynamics of suicide risk (i.e., when suicide occurs). The fluid vulnerability theory conceptualizes suicide as an inherently dynamic construct that follows a nonlinear time course. Newer research implicates the existence of multiple nonlinear change processes among suicidal individuals, some of which appear to be associated with the emergence of suicidal behavior. The cusp catastrophe model provides a useful model for conceptualizing these change processes and provides a foundation for explaining a number of poorly understood phenomena including sudden emergence of suicidal behavior without prior suicidal planning. The implications of temporal dynamics for suicide-focused theory, practice, and research are discussed.